2012
DOI: 10.1258/jtt.2012.120416
|View full text |Cite
|
Sign up to set email alerts
|

Malpractice claims regarding calls to Swedish telephone advice nursing: what went wrong and why?

Abstract: We analysed the characteristics of all malpractice claims arising out of telephone calls to Swedish Healthcare Direct (SHD) during 2003-2010 (n = 33). The National Board of Health and Welfare's (NBHW) investigations describing the causes of the malpractice claims and the healthcare providers' reported measures were analysed using Qualitative Content Analysis. The original telephone calls themselves, which had been recorded, were analysed using the Roter Interaction Analysis System (RIAS). Among the 33 cases, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(106 citation statements)
references
References 14 publications
3
103
0
Order By: Relevance
“…This can be due to earlier contentment with the service or linking the telenursing power [37] with a trust in telenurses' correct assessment. However, telenurses are not infallible, and parents' blind adherence to a telenurse's recommendations may in some cases delay children's treatments and possibly lead to adverse events [55] . In these situations, minority ethnic groups are possibly at higher risk due to reports of ethnic disparities in access to timely, high-quality emergency care [56] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be due to earlier contentment with the service or linking the telenursing power [37] with a trust in telenurses' correct assessment. However, telenurses are not infallible, and parents' blind adherence to a telenurse's recommendations may in some cases delay children's treatments and possibly lead to adverse events [55] . In these situations, minority ethnic groups are possibly at higher risk due to reports of ethnic disparities in access to timely, high-quality emergency care [56] .…”
Section: Discussionmentioning
confidence: 99%
“…This has however not been explored in the present study. To assure safer pediatric care and avoid the risk of malpractice claims [55] , telenurses' usage of safety netting advice, that is to encourage parents to call back or contact emergency services whenever necessary, is specifically important.…”
Section: Relevance For Clinical Practicementioning
confidence: 99%
“…Anxiety, aggravating factors in the caller's previous medical history, or surrounding environment (such as long distance to medical attention) can be one reason for such a request. From a patient safety point of view, such callers identify a need for medical attendance which might be correct, and which needs to be explored by telenurses [18] .…”
Section: Discussion and Reflectionsmentioning
confidence: 99%
“…It has recently been shown that in a group of callers with a preconception of care level, surprisingly few callers were asked about their own opinion of being triaged to a lower level of care. This could be regarded as a nurse-driven agenda in contrast to a patient-centred agenda [18] . Callers in the present study openly requested a change in this direction in their free written comments.…”
Section: Discussion and Reflectionsmentioning
confidence: 99%
See 1 more Smart Citation